2017
DOI: 10.1021/acscatal.7b03812
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Benzazepines from Benzylamines and MBH Adducts Under Rhodium(III) Catalysis via C(sp2)–H Functionalization

Abstract: The rhodium­(III)-catalyzed cross-coupling reaction between commercially available benzylamines and Morita–Baylis–Hillman (MBH) adducts is described. This protocol provides a facile access to various 2-benzazepine derivatives via the C­(sp2)–H activation of N-allylated benzylamines and subsequent intramolecular olefin insertion followed by N-allylation reaction. A range of substrates has been used, and a high level of chemoselectivity as well as functional group tolerance was observed. To gain mechanistic insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…In these transformations, we observed that the ester functionality on MBH adducts can lower the energy barrier of the migratory insertion step, hence enhancing the catalytic cycle. On the other hand, allyl acetate was inactive under the identical reaction condition, which was supported by DFT calculations . These results indicate that the electron density on olefin moiety is crucial for the success of the reaction.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…In these transformations, we observed that the ester functionality on MBH adducts can lower the energy barrier of the migratory insertion step, hence enhancing the catalytic cycle. On the other hand, allyl acetate was inactive under the identical reaction condition, which was supported by DFT calculations . These results indicate that the electron density on olefin moiety is crucial for the success of the reaction.…”
Section: Methodssupporting
confidence: 54%
“…Alkenes have been intensively studied for the formation of heterocyclic compounds in C−H functionalization event involving the nucleophilic addition of directing groups to olefinic moieties or the electrophilic addition of directing groups to M−C intermediates. Very recently, our group disclosed the Rh III ‐catalyzed C−H functionalization and in situ annulation reaction using Morita–Baylis–Hillman adducts to afford 2‐benzazepines, bridged benzoxazepines, and 2‐naphthols . In these transformations, we observed that the ester functionality on MBH adducts can lower the energy barrier of the migratory insertion step, hence enhancing the catalytic cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Seven-member heterocyclic scaffolds, especially azepines or their derivatives have attracted considerable attention by virtue of their interesting biological properties. [109,110] Kim's group in 2017 reported another interesting Rh(III)-catalyzed cross-coupling reaction between benzylamines and Morita-Baylis-Hillman (MBH) adducts to build a wide range of 2benzazepine derivatives (Scheme 31) [112]. This transformation has a good chemoselectivity as well as high functional group tolerance.…”
Section: Construction Of Seven-member Heterocyclesmentioning
confidence: 99%
“…between benzylamines and Morita-Baylis-Hillman (MBH) adducts to build a wide range of 2benzazepine derivatives (Scheme 31) [112]. This transformation has a good chemoselectivity as well as high functional group tolerance.…”
Section: Construction Of Seven-member Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation